Relationship between social media addiction and impulsivity in schoolchildren of public educational institutions in East Lima - Campos Bartolo, Laura (2019)
Objective: To determine the relationship between addiction to social networks and impulsiveness inthe students of 4th and 5th grade of secondary school of two state educational institutions of East Lima.Methodology: Non-experimental design, quantitative approach, cross-sectional and correlational type.The measurement of the impulsivity variable was the Barratt Impulsivity Scale in early adolescents (BIS-11-A) which contains two dimensions: general impulsivity and unplanned impulsivity. Regarding thesocial network addiction variable, the Social Network Addiction Risk Scale (CrARS) was used, whichcontains seven dimensions, prepared by Vilca and Vallejos (2015). Results: The sample consistedof 253 students, of both sexes, whose ages were 15-17 years. A significant relationship was foundbetween impulsivity and social media addiction (rho = .445, p <.01). Conclusion: That students whohave high levels of impulsivity are related to a higher risk of addiction to social networks